Latitudinal changes in siphonophore assemblages across the Atlantic sector of the Southern Ocean. Issue 2 (2nd April 2020) - Kuyper, D; Thibault, D; Gibbons, MJ
Abstract : Siphonophores are commonly considered to be useful indicators of water masses and water-mass movement, but their employment as such across the wider Southern Ocean has not so far been attempted. We redress this here using archived samples, collected during January–February 1993 along a transect from Cape Town to the South African National Antarctic Expedition (SANAE) base in Antarctica, and compare the patterns generated with those determined from a prior analysis of whole assemblages at lower taxonomic resolution. Twenty-one species were identified from 18 of the original 53 samples collected, and two distinct assemblages were confirmed as separated by the Sub-Antarctic Front. That to the south was characterised by low diversity and high abundance and was dominated by cold-water specialists, whereas that to the north comprised a larger number of subtropical and temperate species at low abundance. Assemblage structure was strongly influenced by the mixed layer depth, sea surface salinity and chlorophyll a concentration, as well as mesozooplankton biomass. Congruence with the whole-assemblage study was high, indicating that this taxon can be suitably employed as a proxy in studies such as this. The study emphasises the value of archived plankton samples and makes a plea for better curation.